VD_FINDINFO ML / 2012 / 61 vom 8. Februar 2012 - VD Tribunal cantonal (2012)
MAINLEVÉE DÉFINITIVE, COTISATION AVS/AI/APG, DÉCISION DE COTISATIONS | 80 LP, 54 al. 1 LPGA, 34a RAVS, 41bis al. 1 let. a RAVS